Sustainable Religious Tourism: A Systematic Literature Review - Khoiriyah, Nuzulia; Pujiyanto, Eko; Damayanti, Retno Wulan; Yuniaristanto, Y (Universitas Muhammadiyah Surakarta, 2024)
The study explores the dual impacts of tourism in the religious sector, highlighting both its positive contributions and environmental challenges when sustainability principles are disregarded. A literature review employing the PRISMA method examined 55 articles from SCOPUS-indexed journals published between 2014 - 2024, resulting in 27 relevant articles on the sustainable religious tourism field. Findings underscored that religious tourism generates social, economic, and environmental impacts. A comprehensive management framework is advocated for sustainable religious tourism, necessitating collaboration among stakeholders. Central to this approach is balancing the interests of all stakeholders to mitigate conflicts of interest effectively. The study recommends formulating and implementing a religious tourism sector strategy. This involves defining management concepts, executing strategies, and enforcing supervision mechanisms to foster sustainable practices.